2005
DOI: 10.1021/ja0532281
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity in Platinum-Catalyzed cis−trans Carbon−Carbon Double-Bond Isomerization

Abstract: The isomerization of trans-2-butene to its cis conformer was found to be easier on Pt111 surfaces than the opposite cis to trans conversion. This kinetic trend, which is opposite to what would be expected on thermodynamic grounds, is explained by an increased stability of the cis isomer upon adsorption. A model where adsorption energies are affected by steric interactions between the side moieties of the olefin and the surface suggests that selectivity toward cis versus trans formation may be manipulated by co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
79
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 15 publications
9
79
3
Order By: Relevance
“…[1][2][3] This is a surprising result that runs counter to thermodynamic expectations, and not what is usually observed in alkene catalytic conversions. 4,5 It was hypothesized that the cis-trans isomerization reversal may be associated with structural details of the surface, which could therefore be used to tune selectivity in catalysis.…”
contrasting
confidence: 65%
See 1 more Smart Citation
“…[1][2][3] This is a surprising result that runs counter to thermodynamic expectations, and not what is usually observed in alkene catalytic conversions. 4,5 It was hypothesized that the cis-trans isomerization reversal may be associated with structural details of the surface, which could therefore be used to tune selectivity in catalysis.…”
contrasting
confidence: 65%
“…4,5 It was hypothesized that the cis-trans isomerization reversal may be associated with structural details of the surface, which could therefore be used to tune selectivity in catalysis. 1 The quantummechanical calculations reported here provide a molecular-level picture of the factors that control selectivity in these reactions. Two observations stand out from the data reported below: (1) selectivity is heavily influenced by the coverage of the coadsorbed hydrogen atoms present on the surface, and (2) the relative stability of the cis vs trans olefins on surfaces depends not only on the energies of molecular deformations and alkene-surface interactions but also on those associated with surface restructuring.…”
mentioning
confidence: 97%
“…isomerization of 1-butene to iso-butene [5][6][7][8] and the trans-cis isomerization of 2-butene [9][10][11][12]. Some earlier studies [13] focused on the thermodynamic date and reaction mechanism of 1-butene isomerization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…In another example, the dehydrogenation of cyclohexene was found to be faster on Pt (111) than on Pt (100) single-crystal surfaces (16). Our recent surface-science investigations on the isomerization of unsaturated olefins (17)(18)(19) strongly suggest that selectivity toward the formation of the cis isomer may be favored by Pt (111) facets. Additional surfacescience reports on the conversion of alkyl and alkene adsorbates under vacuum conditions (20)(21)(22)(23)(24)(25), as well as studies with more realistic model systems (26,27), point to a potential structure sensitivity in the conversion of other olefins and unsaturated hydrocarbons.…”
mentioning
confidence: 96%
“…Although the conversion of alkenes by transition metals is one of the oldest and most studied systems in catalysis (51)(52)(53), key issues such as the dependence of activity on structure remain unresolved (54). As mentioned in our Introduction, results from recent surface-science work in our laboratory have indicated that, at least on Pt (111) single-crystal surfaces, the isomerization of trans-2-butene to its cis isomer is easier than the opposite cis-totrans conversion (17)(18)(19). A kinetic study on the catalytic conversion of butenes on single-crystal surfaces (55) has also suggested different selectivities on Pt (111) vs. Pt (100) surfaces.…”
mentioning
confidence: 99%